The long-term effects of crop diseases on education and earnings - Yuri Barreto; Rodrigo Carvalho Oliveira (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
The economic literature has shown that exogenous transitory shocks affect education by changing the opportunity cost of children. We argue that this is only part of the explanation. When permanent, shocks may change contracts and the organization of labour by eroding the productive structure and decreasing land values. This paper studies the long-term effects of a longlasting environmental shock on individuals' educational achievement and earnings. We investigate the 1988 witches' broom outbreak in Brazil, the world's second-leading cocoa producer at the time. Our results show that crop disease negatively impacted the long-term education and earnings of exposed cohorts living in affected areas. Our findings suggest that an increase in child labour and family farm work, driven by changes in labour contracts and land use, could explain the results. Also, the prevalence of a type of contract frequently tied to modern slavery and child labour, known as meeiros (sharecroppers, in English), increased.
Keywords: N36; O12; O15; 330; witches' broom; long-term; education; earnings; child labour